Drug treatment strategies for depression in Parkinson disease. (24th July 2019) - Ryan, Melody; Eatmon, Courtney V.; Slevin, John T.
ABSTRACT: Introduction : Depression is a common non-motor symptom in Parkinson disease (PD), occurring in approximately 20% of patients with PD. While depression can occur anytime in the disease process, it predates PD diagnosis in about 30% of patients. Between 20% and 60% of depressed patients with PD are either without recognition or treatment of their depression. Areas covered : The pathophysiology of depression in PD is unclear. There are several structural changes seen in depressed patients with PD that are also seen in patients with depression. In addition, the neurotransmitters dopamine, serotonin, and norepinephrine are all depleted in PD. This article covers the pharmacological treatment of depression in PD; this involves standard antidepressant treatment such as selective serotonin reuptake inhibitors, tricyclic antidepressants, serotonin and norepinephrine reuptake inhibitors, and monoamine oxidase inhibitors. As with depression not associated with PD, most treatment is partially successful. Non-pharmacological approaches are also touched upon. Expert opinion : Most antidepressant therapy shows partial efficacy in patients with PD. However, there is a need for better study design as well as more comparative studies for the treatment of depression in PD. Biomarkers will help identify patients with PD and depression earlier in the future.